The incidence of different forms of ileus following surgery for abdominal birth defects in infants: a systematic review with a meta-analysis method - Eeftinck Schattenkerk Laurens D.; Musters Gijsbert D.; Nijssen David J.; de Jonge Wouter J.; de Vries Ralph; van Heurn L.W. Ernest; Derikx Joep P.M. (Innovative Surgical Sciences, 2021)
Ileus following surgery can arise in different forms namely as paralytic ileus, adhesive small bowel obstruction or as anastomotic stenosis. The incidences of these different forms of ileus are not well known after abdominal birth defect surgery in infants. Therefore, this review aims to estimate the incidence in general between abdominal birth defects.